Research on Visual Servo Grasping of Household Objects for Nonholonomic Mobile Manipulator - Huangsheng Xie; Guodong Li; Yuexin Wang; Zhihe Fu; Fengyu Zhou (Journal of Control Science and Engineering)
This paper focuses on the problem of visual servo grasping of household objects for nonholonomic mobile manipulator. Firstly, a new kind of artificial object mark based on QR (Quick Response) Code is designed, which can be affixed to the surface of household objects. Secondly, after summarizing the vision-based autonomous mobile manipulation system as a generalized manipulator, the generalized manipulator’s kinematic model is established, the analytical inverse kinematic solutions of the generalized manipulator are acquired, and a novel active vision based camera calibration method is proposed to determine the hand-eye relationship. Finally, a visual servo switching control law is designed to control the service robot to finish object grasping operation. Experimental results show that QR Code-based artificial object mark can overcome the difficulties brought by household objects’ variety and operation complexity, and the proposed visual servo scheme makes it possible for service robot to grasp and deliver objects efficiently.